2014
DOI: 10.7600/jpfsm.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of intestinal iron absorption: Iron-deficient mucosal cells respond immediately to dietary iron concentration

Abstract: Iron is a nutrient and its deficiency is the most frequent nutritional disorder worldwide, occurring in 4 to 5 billion people corresponding to about 70-80% of the world's population as estimated by the World Health Organization. However, an excess of iron increases oxidative stress and increases the risk of death and cancer; thus blood transfusion and supplementation should be used with caution. As there is no mechanism for deliberate iron excretion, the regulation of iron absorption in the small intestine is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“… 26 27 Some evidence points to changes in gastrointestinal epithelial cells following a large bolus of iron that results in reduced transport of iron into portal blood. 28 A prior meta-analysis of 21 trials concluded that, compared with daily iron supplements, intermittent supplementation had similar effects on haemoglobin levels but was less effective in reducing anaemia. 29 Our findings, based on a much larger number of trials, suggest that frequent and intermittent supplementation are similarly effective in reducing anaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 27 Some evidence points to changes in gastrointestinal epithelial cells following a large bolus of iron that results in reduced transport of iron into portal blood. 28 A prior meta-analysis of 21 trials concluded that, compared with daily iron supplements, intermittent supplementation had similar effects on haemoglobin levels but was less effective in reducing anaemia. 29 Our findings, based on a much larger number of trials, suggest that frequent and intermittent supplementation are similarly effective in reducing anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since mammalian gastrointestinal epithelial cells turn over every 2–6 days, weekly supplementation may not be at a great disadvantage relative to daily supplementation with respect to the total amount of absorbed iron 26 27. Some evidence points to changes in gastrointestinal epithelial cells following a large bolus of iron that results in reduced transport of iron into portal blood 28. A prior meta-analysis of 21 trials concluded that, compared with daily iron supplements, intermittent supplementation had similar effects on haemoglobin levels but was less effective in reducing anaemia 29.…”
Section: Discussionmentioning
confidence: 99%